Familial myasthenia gravis. Issue 9 (September 1982) - Honeybourne, D; Dyer, P A; Mohr, P D
Abstract : A family is reported in which myasthenia gravis and thyroid disease occur over three generations. The grandmother and granddaughter have ocular myasthenia and an aunt in the second generation had generalised myasthenia gravis with a thymoma. The pattern of histocompatibility antigens (HLA) haplotypes, anti-AChR antibodies, anti-striate muscle antibodies and thyroid disease is described. The haplotype HLA-A1, B8 was found in affected members of the first and third generation but the family study showed that this was not the same haplotype because the HLA-A1, B8 haplotype in the third generation was contributed by an unaffected person marrying into the family in the second generation.